2001
DOI: 10.1161/hc5001.100793
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Coagulation and Fibrinolytic Proteins and Their Relation With Acute Myocardial Infarction

Abstract: Background-It is pathophysiologically conceivable that genetic variations in coagulation and fibrinolytic proteins are associated with the risk of myocardial infarction. Methods and Results-We performed a literature search to identify published case-control studies correlating the factor V Leiden or prothrombin G20210A mutations or fibrinogen GϪ455A or plasminogen activator inhibitor-1 (PAI-1) 4G/5G polymorphisms with the risk of myocardial infarction. Studies were included only if they used solid diagnostic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
126
4
7

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(144 citation statements)
references
References 58 publications
7
126
4
7
Order By: Relevance
“…Moreover, at least 37 separate studies have detected significant allelic dose-dependent correlations between carriage of the 4G allele and PAI1 protein levels in vivo, such that 4G4G homozygotes have the highest levels of circulating PAI1, 5G5G homozygotes have the lowest levels, and heterozygous individuals have intermediate levels of circulating PAI1 (Supplementary Table S1). Indeed, multiple studies and meta-analyses have found significant associations between 4G/5G genotypes and various vascular and thrombotic diseases (23)(24)(25)(26)(27)); yet, its role in cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at least 37 separate studies have detected significant allelic dose-dependent correlations between carriage of the 4G allele and PAI1 protein levels in vivo, such that 4G4G homozygotes have the highest levels of circulating PAI1, 5G5G homozygotes have the lowest levels, and heterozygous individuals have intermediate levels of circulating PAI1 (Supplementary Table S1). Indeed, multiple studies and meta-analyses have found significant associations between 4G/5G genotypes and various vascular and thrombotic diseases (23)(24)(25)(26)(27)); yet, its role in cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies including different ethnic groups, such as Afro-Caribbeans, 7 Asians, 7 Pima Indians, 8 or Japanese, 9 have reported different frequencies of the 4G allele from those in non-Hispanic whites, as well as differences in the relation of the 4G/5G genotype to circulating levels of PAI-1. 8 The 4G/5G genotype has been related to the risk of myocardial infarction (reviewed in Boekholdt et al 10 ), sudden cardiac death, 11 transplant coronary artery disease, 12 and in-stent restenosis after coronary stent implantation. 13 These studies have focused on non-Hispanic whites.…”
mentioning
confidence: 99%
“…Most polymorphisms of the coagulation system proteins involved with venous thrombosis present little or no association with an AMI 14 . In Brazil, Faria-Neto et al 15 demonstrated a low prevalence and no correlation of Factor V Leiden and prothrombin G20210A and methylenetetrahydrofolate redutase C677T (involved in…”
Section: Discussionmentioning
confidence: 98%